Rice Prices Volatility in Indonesia: Describing the Inurement of Domestic Production and Large-Scale Imports - Hendy Febrianto Kurniawan; Mohamad Dian Revindo; Rizky Deco Praha; Naufal Zaki Arrafif (Journal of Economics and Business, 2026)
In spite of its stated objectives in agriculture towards self-sufficiency drive ever since becoming independent, Indonesia remains reliant to importing rice for domestic needs. As the international rice market becoming more volatile in recent years, it is imperative to fundamentally analyse the dynamics between trade policies and domestic market equilibrium. By employing a qualitative-descriptive approach, this study aims to provide a specific picture of the situation, phenomenon, or social symptoms of the role of government rice importation in domestic rice market activities, including price transmission and community production. We find that the increase of import in times of high prices are not necessarily reflected on consumer prices, instead they tend to depresses prices on farmers level. Price movements correlate more strongly with a surge in supply during harvest periods. Through the findings, we suggest reassessment of trade policies, farmer-oriented policies, logistical infrastructures, and support mechanisms for domestic production and import management.